Makna Lagu “Tikus-Tikus Kantor” Oleh Iwan Fals - Eef Rokhmansyah (Student Scientific Creativity Journal, 2023)
This article analyzes the interpretations and metaphors on the lyric of Iwan Fals song. This research was also conducted using the hermeneutic approach which showed that is was descriptive. There are also metaphors used in the "Tikus-tikus Kantor" song such as mice, cats and shrimp. One of the interesting thing is that the lyrics of this song are not expressed clearly but uses figure of speech. Research has shown that the song is about public criticism of corruption by government officials and law enforcement agencies.